PENINGKATAN MINAT MENULIS PUISI SISWA MELALUI GERAKAN LITERASI - Saenal Masri; Ratnawati; Aco Karumpa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research discusses increasing students' interest in writing poetry through the literacy movement at school. This research aims to analyze the influence of literacy activities, such as poetry workshops and writing competitions, on students' motivation to express themselves through poetry. The method used is qualitative-descriptive, with data collection through observation and interviews with students and teachers. The research results showed that the literacy movement succeeded in increasing students' interest in writing poetry, where students felt more motivated to participate in creative activities. Apart from that, support from the school environment, such as teacher guidance and space to share work, also contributes to the development of students' poetry writing abilities. This article concludes that the literacy movement is effective in generating students' creativity and interest in literature, especially poetry.